INTEGRASI NILAI-NILAI ISLAM DALAM PROSES PENELITIAN ILMIAH - Jeny Rheka; Nurul Ilmi Adyana; Andi Fitriani Djollong; Nur Amalina Abdul Rahman; Nur Aliah; Sudirmanto Sudirmanto (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the integration of Islamic values in the scientific research process in terms of epistemological, methodological, and ethical aspects, as well as its implications for the quality and integrity of research results. Method: This study uses a qualitative approach with a type of library research that is descriptive-analytical. Data were obtained from the Qur’an, hadith, books, scientific journals, and other relevant literature, then analyzed using content analysis techniques. The abstract is important because many journal readers read the abstract first to determine whether the entire article is worth reading. Results: The study results indicate that the integration of Islamic values forms a holistic and integrative scientific paradigm through a combination of revelation, reason, and empirical experience as sources of knowledge. The implementation of Islamic values is reflected in the principles of honesty, trustworthiness, justice, objectivity, and scientific responsibility. These values contribute to increasing the validity, credibility, and integrity of research, as well as serve as a preventive effort against various forms of academic misconduct, such as plagiarism and data manipulation. Novelty: This study offers a conceptual framework for the integration of Islamic values that not only serves as an ethical foundation but also as an epistemological and methodological basis in the conduct of scientific research oriented towards truth, public benefit, and spiritual responsibility